Analysis of water hammer by using pipenet software and manual methods / Shaida Fatha Idris - Idris, Shaida Fatha (2018)
The lack of knowledge about water hammer phenomenon among engineers and operators can contribute to frequent occurrence of water hammer in industry. Water hammer is known can cause accident such as rupture of the pipe, flange and other components in the piping system or even explosion. Due to the impacts of water hammer, the safety officers from the industry together with the engineering consultant in this major have come out with variety methods that can reduce or eliminate the water hammer impact and occurrence. In this report, the methods used including the Pipenet software simulation and manual calculations. There are two objective of this report which are to investigate the effect of pipe length, valve closure rate and fluid flow rate on the surge pressure inside a closed conduits and to determine the applicable method in reducing the surge pressure. From the results obtained, the pressure surge recorded was becoming high as shorter pipe, rapid valve closure and higher fluid flow rate was used. As for the second objective, the installation of accumulator tank was found to be the most applicable method due to minimum cost and the effectiveness in mitigating the water hammer which at about 70% effectiveness. Therefore, it is proven that surge pressure or water hammer is affected by various factor such as pipe length, valve closure rate and fluid flow rate and many prevention methods exist but analysis shall be done before applying it to achieve optimum performance and costing.